2011
DOI: 10.1158/1078-0432.ccr-10-2107
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Chaperones as a Common Set of Proteins That Regulate the Invasion Phenotype of Head and Neck Cancer

Abstract: Purpose: The goal of this study was to establish a common set of molecules that regulate cell invasion in head and neck cancer (HNC).Experimental Design: Five invasive sublines derived from HNC cell lines were established using the Matrigel selection method. Proteomic technology, MetaCore algorithm, and reverse transcriptase-PCR methods were used to search for molecules that contribute to the invasion phenotype. Cellular functional analyses and clinical association studies were applied to examine the significa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 49 publications
2
53
0
Order By: Relevance
“…Interestingly, we found downregulation of the glucosidase II alpha subunit GANAB (fold change = −11.28) and Core2/Core4 beta‐1,6‐N‐acetylglucosaminyltransferase GCNT3 (fold change = −3.55) (Appendix Fig S3A). Downregulation of both these genes has been previously shown to lead to enhanced cell migration and invasion, resulting in aggressive cancers, consistent with our results showing FUT9 knockdown leads to increased colony formation and cell migration (Fig 3D and F) (Huang et al , 2006; Chiu et al , 2011). Previous studies in colorectal cancer have shown that higher levels of core 1 glycans, T antigen, and Tn antigen are the most predominantly observed O‐glycosylation changes (Holst et al , 2015).…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, we found downregulation of the glucosidase II alpha subunit GANAB (fold change = −11.28) and Core2/Core4 beta‐1,6‐N‐acetylglucosaminyltransferase GCNT3 (fold change = −3.55) (Appendix Fig S3A). Downregulation of both these genes has been previously shown to lead to enhanced cell migration and invasion, resulting in aggressive cancers, consistent with our results showing FUT9 knockdown leads to increased colony formation and cell migration (Fig 3D and F) (Huang et al , 2006; Chiu et al , 2011). Previous studies in colorectal cancer have shown that higher levels of core 1 glycans, T antigen, and Tn antigen are the most predominantly observed O‐glycosylation changes (Holst et al , 2015).…”
Section: Resultssupporting
confidence: 92%
“…HYOU1 is expressed in many different cell types and can be upregulated by various cellular conditions, including hypoxia and ER stress (32,33). Furthermore, HYOU1 is upregulated in some human cancers, including head and neck and breast cancers (34,35). The HYOU1 transcript was originally cloned from astrocytes under hypoxic conditions (36), which makes it a protein relevant to KSHV biology, since hypoxia plays a role in the KSHV life cycle (37).…”
mentioning
confidence: 99%
“…Cell migration is a complex process that integrates different protein-protein interactions and signaling events, and includes focalized adhesion dynamics and the remodeling of the structure of the actomyosin skeleton [9]. The potential role of HSPs and other chaperones in this process might be considered because they are involved both in functions of cytoskeleton [22] and metastasis [4,25,38]. Hence, we can not exclude that HSF1-regulated HSPs play a role in our experimental model.…”
Section: Discussionmentioning
confidence: 99%